PENGEMBANGAN SRATEGI PEMASARAN PERUSAHAAN KEUANGAN DALAM MENINGKATKAN KEUNGGULAN BERSAING - DATIN NADLIROH, INDAH; EKA RAMADHANI, FERRA (STIEKOP MALANG PRESS, 2025)
Purpose – The purpose of developing a marketing strategy for a financial company is to enhance its competitive advantage within the market. This involves identifying target audiences, crafting compelling value propositions, and implementing effective channels to attract and retain customers, ultimately differentiating the company from its competitors and securing a stronger market position. Design/methodology/approach – This research will employ a mixed-methods approach to develop marketing strategies for financial institutions seeking to enhance competitive advantage. The methodology will involve both qualitative data collection through interviews with key industry stakeholders and quantitative analysis of market trends and competitor performance. This combined approach will enable the formulation of actionable strategies grounded in both expert insights and empirical evidence. Findings – The research indicates that developing a comprehensive marketing strategy is crucial for financial institutions seeking to bolster their competitive advantage. Key findings likely encompass specific marketing tactics, target audience identification, and competitive landscape analysis that contribute to enhanced market positioning and overall business success. Research limitations/implications – This research on developing marketing strategies for financial firms to enhance competitive advantage is limited by its specific focus on a single industry, potentially restricting the generalizability of findings to other sectors. Furthermore, the study's reliance on [Mention specific data collection methods, e.g., survey data, case studies] may introduce bias or limit the depth of insights. However, the findings offer valuable practical implications for financial institutions seeking to refine their marketing approaches and gain a stronger market position, highlighting the importance of customer segmentation, digital marketing integration. Future research could explore the application of these strategies in diverse industries or utilize alternative methodologies for a more comprehensive understanding. Originality/value – Developing marketing strategies for financial companies to enhance competitive advantage requires a focus on originality and value. Innovative approaches, tailored to specific customer segments and leveraging emerging technologies, are crucial for differentiation. Creating tangible value for customers through transparent communication, personalized offerings, and exceptional service delivery further solidifies competitive positioning and fosters long-term loyalty.